2017
DOI: 10.1039/c6ra28721b
|View full text |Cite
|
Sign up to set email alerts
|

A simple 3D cryogel co-culture system used to study the role of CAFs in EMT of MDA-MB-231 cells

Abstract: Development of a 3D co-culture system for the study of the role of CAFs in the EMT process of MDA-MB-231 cells in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…After that, they used the co-culture human breast cancer system to construct a xenograft tumor mouse model for in vivo studies. The results showed that carcinoma-associated fibroblasts could also promote deterioration and metastasis of human breast cancer cells in a xenograft tumor [70].…”
Section: Composite Cryogels As Versatile Tools For Biomedical Applmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, they used the co-culture human breast cancer system to construct a xenograft tumor mouse model for in vivo studies. The results showed that carcinoma-associated fibroblasts could also promote deterioration and metastasis of human breast cancer cells in a xenograft tumor [70].…”
Section: Composite Cryogels As Versatile Tools For Biomedical Applmentioning
confidence: 99%
“…The co-culture system for the role of carcinoma-associated fibroblasts in the epithelial–mesenchymal transition process of human breast cancer cells in vitro and in vivo. Republished with permission from [70]. Copyright 2017 the Royal Society of Chemistry.…”
Section: Figurementioning
confidence: 99%
“…Cryogels formed from PEG-heparin have been reported by our group (Bray et al, 2018), where they were used to create a bone microenvironment using mineralized primary human osteoblasts for co-culture with breast cancer cells lines. Another study utilized a gelatin-based cryogel modified with methacrylate groups (GelMA) (Zhang et al, 2017). The authors used the cryogels to create a tumor stromal microenvironment using CAFs derived from breast cancer patients, showing increased cancer cell migration compared to their mono-cultures.…”
Section: Engineering Patient-specific Tumor Microenvironment Modelsmentioning
confidence: 99%
“…Along with their use as scaffolds for tissue regeneration, 18,[20][21][22] cryogels are also being increasingly explored to develop 3D functional tumor models in vitro. [23][24][25][26] Since cancer cell growth is modulated by the stiffness of the surrounding matrix, with cancerous tissues being generally stiffer than non-malignant tissues, 23,27 cryogels may indeed be useful to mimic the strength and the elasticity of tumors, thus allowing to analyze the biomechanical cues involved in cell-matrix interactions and pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…), which suffer from large batch-to-batch variability and need particular handling care, thus making experimental reproducibility harder to achieve. In this scenario, PEG-based hydrogels 32,[37][38][39][40][41][42][43] and cryogels 23,24,26 appear as powerful alternatives to conventional organotypic culture models for the production of reproducible tumor tissue equivalents.…”
Section: Introductionmentioning
confidence: 99%